Using Authentic and Simplified Texts with SQ3R in Teaching Vocabulary and Reading - Soma, Robi (LINGUA: Jurnal Bahasa dan Sastra, 2014)
The objectives of the study were to find out whether or not (1) there was a significant increase of students achievement in vocabulary and reading literacy after they were taught using SQ3R with authentic texts and simplified texts (2) there was any significant difference in the students achievement in vocabulary and reading literacy between the students who were taught using SQ3R with authentic texts and simplified texts, and (3) there was a significant interaction of authentic texts and simplified texts toward reading literacy and vocabulary mastery of the students who were high and low achievers. Factorial experimental design was used in this study because this study involved two parallel groups which became experimental group 1 and 2. The population of this study was 56 six semester students of Jambi University in the academic year 2012/2013. In selecting the sample, TOEFL ITP was administered to the population. The students were categorized into high and low achievers based on the score. 56 students from the two classes were selected as the sample; 16 students were high achievers and 40 students were low achievers which were distributed equally to the two experimental groups. In collecting the data, tests (pre and post-test) were used to both groups. The data of the test results were analyzed using t-test in SPSS 15. The result of independent sample t-test analysis showed that there was no significant difference in students achievement of vocabulary and reading literacy between both experimental groups as well as level of achievement for both high and low achievers.